Property and Power in a City - McCrone, David. author. aut Link
IX, 240 p.
Keywords: A study of the way landlordism has operated in Edinburgh over the past 100 years. It examines the type of people who have profited from this type of investment and the way they have influenced the city's politics. It is argued that in the long run this is a most destructive form of capitalism.